دور الأساليب الحديثة للمحاسبة الإداريية في تحليل ميزة تنافسية للمؤسسات الإقتصادية - حمزة نصايبية; زين الدين بن عطية (My University, 2022)
This study aimed to identify the contribution of modern methods of management accounting to achieving a competitive advantage for economic institutions, as the latter were developed to keep pace with development and continue their activities at a time characterized by intense competition because they work to maximize their market value and achieve a competitive advantage and work to improve them constantly. Through the application of modern methods of managerial accounting that reduce and rationalize costs, thus improving the performance of institutions, maximizing their market value and improving their competitive advantage. Where the study concluded that the National Oil Corporation is a market unit of Ahras that applies modern methods of managerial accounting such as the method of target cost continuous improvement, the balanced performance card, the method of total quality management and obtaining the ISO 900015 specification for production at the lowest cost and the highest possible profit while ensuring the achievement of a competitive advantage and working to improve it Consistently, the study recommends the necessity of applying the methods in economic institutions. .................................................................